Comparison Effect of Clonidine and Magnesium Sulfate on Bleeding Volume during Septorhinoplasty: A Double-Blind, Randomized Clinical Trial - Seyed Babak Mojaveraghili; Fatemeh Talebi; Nasser Behnampour (Archives of Anesthesia and Critical Care)
Background: Control of hemodynamic changes and blood loss is a daily challenge in general anesthesia for patients undergoing septorhinoplasty. This study aimed to evaluate the effects of magnesium sulfate and clonidine on the control of hemodynamic factors and bleeding volume during this procedure. Methods: This double-blind, randomized clinical trial study was conducted on 60 patients undergoing septorhinoplasty at 5th Azar Medical & Educational Centre of Gorgan in 2021-2022. Patients were divided into two intervention groups (50 mg/kg of magnesium sulfate) and control group (5 μg/kg of clonidine) with permutation random block allocation. All patients underwent induced hypotension. Before induction of anesthesia and every 5 minutes afterwards, blood pressure was recorded. Blood loss volume was calculated at the end of the surgery. Results: In the magnesium group, 36 individuals were evaluated, while in the clonidine group, 24 individuals were examined. There were no statistically significant differences in baseline characteristics of patients in the two groups and the duration of surgery. Both drugs were equally effective in inducing hypotension, however blood pressure changes in magnesium group were more trivial than clonidine group. The bleeding volume in the magnesium sulfate and clonidine groups was 139.44 ml and 141.25, respectively and this difference was not statistically significant (p-value=0.634). Conclusion: The results of this study showed that magnesium sulfate can be effectively used as an alternative to clonidine in controlling hemodynamic changes and ultimately reducing blood loss volume during septorhinoplasty surgery. In addition, magnesium is at least as effective as clonidine in stabilizing hemodynamic changes.